Altruistic Leadership Style in Education: Implications for Policy and Practice - Purnomo, Sigit Hadi; Anatasya, Ledya (Development: Studies in Educational Management and Leadership, 2024)
This study critically examines how altruistic leadership shapes the school environment and students’ character development in a madrasah context.  Using a qualitative case study design, data were collected through in-depth semi-structured interviews with the principal, teachers, and student representatives from MAN 1 Bekasi. Findings indicate that altruistic leadership creates a supportive institutional climate, increases students' intrinsic motivation, and strengthens collaboration between educators and parents. The study also identified implementation challenges—such as aligning values with daily practices and maintaining stakeholder commitment—and proposed strategic interventions to improve efficacy, including structured professional development, shared decision-making, and parent-school engagement programs. These findings provide practical and relevant insights for educational leaders and policymakers seeking to apply altruistic leadership principles to improve standards in madrasah institutions. This study contributes to the educational leadership literature by providing evidence-based recommendations that can be adapted to various madrasah contexts to improve overall educational effectiveness.